Biaxial cyclic behavior of bolted end-plate connection to I-column reformed by box-plates - Yilmaz, Orkun; Bekiroglu, Serkan (ELSEVIER SCI LTD, 2022)
In the research study, different 3D joint concepts of a frame formed by an I-column subjected to the biaxial cyclic load were simulated. Non-linear finite element models using the Ansys software were developed to evaluate the biaxial cyclic behaviors of the joints. After verification via five existing experimental tested beam-to-column connections, six different representative finite element models of the joints, including a 3D corner joint, two 3D edge joints, and two 3D interior joints with the biaxial cyclic load as well as a 2D corner joint as a base specimen with uniaxial cyclic load, were established with and without under axial compression force on the column. A newly developed weak-axis connection detail was implemented to connect the beam to the weak-axis of the column. Two box-plates parallel to the web of the column connected between the flange tips of the I-shaped column were used to reform the region of the I-column corresponding to the beam connection. The four-bolted unstiffened end-plate connection specified in AISC 358-16 was used as the beam-to-column connection in both the strong-axis and the weak-axis directions of the I-shaped column. The results indicate that biaxial loading causes a loss of strength in the early loading cycles compared to uniaxial loading. The strong-axis connection of the 3D corner joint has less ultimate connection rotation and a greater value of rotational stiffness than that of the 2D corner. Moreover, all the connections of the joints possessed good hysteretic curves satisfying the limits given in the ANSI/AISC 341-16. Axial compression force on the column reduced performance parameters of the connections such as plastic rotation capacity, energy dissipation ability, and hysteretic equivalent viscous damping ratio. By the way, the weak-axis connections of the joints are acceptable to consider as partially restrained connections, while the strong-axis connections are fully-restrained.
Keywords: Finite element analysis; Biaxial cyclic loading; Strong -axis connection; Weak-axis connection; Four-bolted unstiffened end-plate connection; WEAK-AXIS; SEISMIC PERFORMANCE; SEMIRIGID BEHAVIOR; DESIGN; Engineering